Neuroimaging Features In Patients With Lacunar Ischemic And Hemorrhagic Stroke - Ravshan Abdurakhmanov (International Journal of Medical Sciences And Clinical Research, 2025)
The aim of this study was to investigate the neuroimaging and ultrasound characteristics of cerebral blood flow in patients with lacunar ischemic (LI) and hemorrhagic stroke (HS). A total of 120 patients were examined, including 80 with LI and 40 with HS. MRI/MSCT, color dopplerography, and transcranial dopplerography (TCDG) were used. It was revealed that LI patients were characterized by predominantly atherosclerotic changes with bilateral stenosis of the main cerebral arteries, decreased LBFV, and thickened IMC, even with moderate blood pressure. Patients with HS were more likely to have high blood pressure and vascular deformation without significant stenosis. The findings highlight the diagnostic value of comprehensive neuroimaging and BCA ultrasound for the differential diagnosis and prognosis of cerebrovascular disorders.